Analysis of top cited papers in library and information science that have stood the test of time - Elia, Emmanuel F; Sife, Alfred S. (University of Dar es Salaam Library Journal, 2019)
Analysis of 10 top cited papers in the field of library and information science was carried out to understand their main characteristics and features such as bibliographic details, authorship collaboration, author affiliation, citation counts and specialty. This list of classic papers was extracted from Google Scholar Metrics in June 2018. These most cited articles were published in 2006 and the list was released in June 2017. The findings indicate that these 10 papers originated from 10 different institutions in six countries mostly in North America and Europe. The number of citations ranged from 410 to 3051, the mean number of authors per article is 2.3 and the mean number of citations per year was 98. Nine out of the 10 articles reported citation analyses. This suggests that LIS research has shifted towards exploring scientific publications and their impact through citation analysis, bibliometrics and scientometrics